Curcumin as a Perspective Protection for Retinal Pigment Epithelium during Autophagy Inhibition in the Course of Retinal Degeneration - Pinelli, Roberto; Ferrucci, Michela; Biagioni, Francesca; Bumah, Violet; Scaffidi, Elena; Puglisi-Allegra, Stefano; Fornai, Francesco (Current Neuropharmacology, 2023)
Defective autophagy in the retinal pigment epithelium (RPE) is involved in retinal degeneration, mostly in the course of age-related macular degeneration (AMD), which is an increasingly prevalent retinal disorder, eventually leading to blindness. However, most autophagy activators own serious adverse effects when administered systemically. Curcumin is a phytochemical, which induces autophagy with a wide dose-response curve, which brings minimal side effects. Recent studies indicating defective autophagy in AMD were analyzed. Accordingly, in this perspective, we discuss and provide some evidence about the protective effects of curcumin in preventing RPE cell damage induced by the autophagy inhibitor 3-methyladenine (3-MA). Cells from human RPE were administered the autophagy inhibitor 3-MA. The cell damage induced by 3-MA was assessed at light microscopy by hematoxylin & eosin, Fluoro Jade-B, and ZO1 immunohistochemistry along with electron microscopy. The autophagy inhibitor 3-MA produces cell loss and cell degeneration of RPE cells. These effects are counteracted dose-dependently by curcumin. In line with the hypothesis that the autophagy machinery is key in sustaining the integrity of the RPE, here we provide evidence that the powerful autophagy inhibitor 3-MA produces dose-dependently cell loss and cell degeneration in cultured RPE cells, while inhibiting autophagy as shown by LC3-II/LC3-I ratio and gold-standard assessment of autophagy through LC3-positive autophagy vacuoles. These effects are prevented dose-dependently by curcumin, which activates autophagy. These data shed the perspective of validating the role of phytochemicals as safe autophagy activators to treat AMD.
Keywords: Phytochemicals